Thiazide‐Induced Acute Interstitial Pancreatitis in a 55‐Year‐Old Male: A Rare Adverse Drug Reaction - Kshitiz Pandey; Ashish Panday; Pratik Pandey; Anand Chaudhary; Sushmita Khanal (Clinical Case Reports)
ABSTRACT Acute pancreatitis is inflammation of the pancreas and is most commonly caused by gallstones, alcohol use, hyperlipidemia, or idiopathic. Drug‐induced acute pancreatitis is relatively rare and often under‐recognized; it accounts for 0.1%–2% of all cases. Among many drugs, thiazide diuretics are infrequently implicated but remain a known cause. We report a case of a 55‐year‐old male who presented with acute epigastric pain, nausea, and vomiting 2 weeks after adding thiazide for persistent secondary hypertension. Laboratory investigations revealed elevated pancreatic enzyme levels, and contrast‐enhanced computed tomography confirmed acute interstitial pancreatitis. Comprehensive evaluation excluded common etiologies including gallstones (ultrasound, CT‐scan, and MRCP), alcohol use (history), and dyslipidemia (normal lipid profile). The temporal relationship between drug initiation and symptom onset made thiazide‐induced pancreatitis a likely diagnosis. Discontinuation of hydrochlorothiazide led to clinical improvement for the patient. This case highlights the importance of considering thiazide‐induced pancreatitis in patients who present with acute pancreatitis when the common risk factors are absent. While extensive investigation to search for other rare causes of acute pancreatitis should be done, prompt recognition and withdrawal of the possible offending agent are essential for patient recovery and prevention of recurrence.